Analisis Yuridis Penetapan Nomor 0549/Pdt.P/2018 PA.Pdg. Tentang Permohonan Pengesahan Pernikahan Non Muslim Di Pengadilan Agama Padang Kelas I A - Mardius, Mardius; Mailiza, Sustri (Normative Jurnal Ilmiah Hukum, 2023)
Law Number 1 of 1974 concerning Marriage states that: "Marriage is valid if it is carried out according to the laws of each religion and belief." Article 7 paragraph (3) of the Compilation of Islamic Law states that: The marriage certificate that can be submitted to the Religious Court is limited to matters relating to: the existence of a marriage in the context of settling a divorce, loss of a marriage certificate, doubts about the validity or not of one of the terms of the marriage , there are marriages that occurred before the enactment of Law Number 1 of 1974, marriages carried out by those who do not have obstacles to marriage according to Law Number 1 of 1974. The marriage is valid if according to their respective religions and beliefs and the marriage is in the presence of the person authorized to do so. For those who are Christians and then convert to Islam, this is regulated in the Compilation of Islamic Law, especially implicitly in Article 7 paragraph (3) letter (c). The formulation of the problem is how the judge considered in determining number 0549/Pdt.P/2018 PA.Pdg. regarding the application for legalization of non-Muslim marriages at the Padang Religious Court class I A and what is the juridical analysis of the determination number 0549/Pdt.P/2018 PA.Pdg. regarding applications for legalization of non-Muslim marriages at the Padang religious court class I A. The approach to the problem in this research is normative juridical, the nature of the research is descriptive research. Data collection techniques include interviews and literature study. Data processing by editing and coding, and qualitative data analysis. The results of the research concluded that the judge's consideration in validating non-Muslim marriages with determination number 0549/Pdt.P/2018 was that the applicant was previously non-Muslim, namely Christian, then the applicant converted to Islam. The applicant is still Muslim and has never been divorced. According to the author, the juridical analysis of the determination of legalization of non-Muslim marriages is based on theories in Islamic law, in the book Al-Muhazzab Juzz II page 52 which states that: "The marriage contract of husband and wife before converting to Islam is valid according to the Sharia', even though they were previously married without a guardian and without witnesses. Because during the time of the Prophet SAW, many husbands and wives converted to Islam and the Prophet SAW legalized their marriage before converting to Islam with his taqrir, without asking them about the conditions for marriage according to Islam to them, such as the requirements for a guardian and two fair witnesses." Then this was strengthened based on the Compilation of Islamic Law Article 7 paragraph (3) letter (c).